독립형 신재생발전 시스템의 효율적인 운영을 위한 배터리 용량산정에 관한 연구 - 신희상(Hee-Sang Shin); 허재선(Jae-Sun Hue); 윤상윤(Sang-Yun Yun) (전기학회 논문지 P권, 67(1), 2018)
This paper presents the method of ESS energy capacity calculation for stand-alone renewable energy generation system consisting of photovoltaic energy. There is almost no power from photovoltaic system during sunless days. So this source is very weak in terms of the power supply reliability. To improve problem of power supply, battery is mainly used Energy Storage System(ESS). The number of sunless days and Depth of Discharge(DOD) is important factor to determine energy capacity of battery. However, a many study for economical design is required due to the high cost of ESS. In this paper, we propose the new method of ESS energy capacity calculation by applying different DOD for operation with and without sun. We determine the Battery capacity using higher DOD of operation during sunless day than the DOD of the normal operation. And we carried out an economic analysis of the calculation results.